Training and organizational effectiveness: moderating role of knowledge management process - Azmawani Abd Rahman; Siew Imm Ng; Murali Sambasivan; Florence Wong (Emerald, 2013)
Purpose – Training alone is not sufficient to enhance organizational effectiveness to a greater level because not all knowledge obtained from the training is properly transferred and applied to the organization. This study aims to investigate whether efforts invested by Malaysian manufacturers in employee training and knowledge transfer affect organizational effectiveness.